Textos narrativos y nivel de comprensión critica en niños de la Institución Educativa Inicial N° 602, San Juan Bautista 2024 - Mermao Pizango, Rosa (2025)
The main objective of this study was to determine the relationship between the level of use of narrative texts and the level of critical comprehension in children at Initial Educational Institution No. 602, San Juan Bautista 2025. This study is characterized by a quantitative approach and adopts a non-experimental, correlational, and cross-sectional research design. The sample consisted of a total of 95 children. For data collection, observation was used, utilizing a structured guide as an instrument. The validity of the instrument was thoroughly evaluated by a group of experts with extensive experience in the field. The results in the Tables show a positive and significant correlation between the use of narrative texts and the level of critical comprehension in children. Furthermore, the two-tailed significance level (Sig.) is 0.00, which is lower than the significance level of 0.05. Therefore, the null hypothesis is rejected and the research hypothesis is accepted.